(untitled) (Eurasian Journal of History, Geography and Economics, 2024)
In the article, economic-geographical factors affecting the development of animal husbandry in ensuring food security, the role of the animal husbandry sector in food security and the main factors affecting its development, including economic, geographical and social factors stated. Economic factors, such as investment, market prices and technological innovation, play a major role in ensuring livestock profitability and product supply. Geographical factors reveal the influence of climate, land resources and natural conditions on animal husbandry. The article also analyzes the strategies for managing economic-geographical factors in the development of animal husbandry and the results that can be achieved in ensuring food security through the effective management of factors.